(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article is devoted to professional and pedagogical activity and its topical issues. The article talks about the professional and pedagogical activity of a vocational education teacher and its peculiar features, about the training of a vocational education teacher in higher educational institutions, about the structural model of a modern vocational education teacher.